Effect of steviosides and system composition on stability and antimicrobial action of sorbates in acidified model aqueous systems - Hracek, V. M. (2010)
The effect of steviosides on sorbate stability and on its antimicrobial action was studied in aqueous systems (pH 3.0). The use of steviosides decreased sorbate destruction in all the systems. Its effect on nonenzymatic browning (NEB) depended on the system composition. From the point of view of microbial stability, the steviosides promoted a slight increase in the minimum inhibitory concentration (MIC) of sorbates against Zygosaccharomyces bailii and Zygosaccharomyces rouxii. However, the main effect of steviosides was the protected action on sorbate destruction. This action was essential to ensure that the preservative residual level was higher than the MIC of the preservative to prevent the growth Z. bailii or Z. rouxii during storage. The results reported highlight that the use of steviosides in aqueous model systems resembling low-calorie sweet products can be useful to protect potassium sorbate (KS) from destruction and depending on the system composition also to decrease browning development.